Using the NBTs to inform institutional understandings of under-preparedness: Implications for admissions criteria - Wilson-Strydom, Merridy (South African Journal of Higher Education, 2016)
This paper presents the results of institutional research conducted at the University of the Free State during the course of 2010. The aim of the study was to explore the ways in which the National Benchmark Tests (NBTs) could be used to assist the university to better understand under-preparedness of first-year students, and to use this understanding to review and improve admissions procedures and criteria. An analysis of Grade 12 results, NBT performance and performance in selected first-year modules was conducted across the full cohort of 2010 first-year students. The paper presents a summary of the research results and concludes with recommendations regarding how the NBTs might support institutional decision making in the area of access and admissions.